KOMUNIKASI INTERPERSONAL GURU DALAM MENINGKATKAN KETERAMPILAN SOSIAL SISWA TUNARUNGU (Studi Kasus di Sekolah Dasar Luar Biasa A.B.C.D Yayasan Suka Dharma Kecamatan Polokarto Kabupaten Sukoharjo) - Kartikaningtyas, Bella; Wangi, Maya Sekar; Hindra, Nurnawati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Every child is unique, there are children who easily perceive external responses, but there are also those who are slow to perceive responses. Nobody wants to be born less than perfect. Deafness of hearing in deaf people has a big impact on the ability to receive information that is developing in society and has an impact on lack of verbal skills, so that in communicating with others, deaf students have language limitations, a lack of vocabulary which results in students needing special media to communicate. Education has an important role in the deaf learning phase to speak and communicate. Interpersonal communication between teachers and deaf students in the teaching and learning process is very influential in improving student’s skills. When they are new students, deaf students tend to be passive aggressive, close themselves off and find it difficult to communicate, and tend to be less sensitive to current social situations. The formulation of the problem in this research is How Teacher Interpersonal Communication Improves the Social Skills of Deaf Students in the A.B.C.D Extraordinary Elementary School, Suka Dharma Foundation, Polokarto District, Sukoharjo Regency. This research aims to determine, describe and analyzse teacher’s interpersonal communication in improving the social skills of deaf students at Suka Dharma Foundation A.B.C.D Special Elementary School, Polokarto District, Sukoharjo Regency. The research method used is descriptive with a qualitative approach. Data collection techniques used in-depth interview techniques with four informants. The results of this research show that the social skills of deaf students based on each indicator proposed by Nandang Budiman are perceived by special school teachers through three main components as a result of interpersonal communication established between teachers as subjects and deaf students as objects resulting in the conclusion that the interactional communication model which was carried out successfully met the criteria for improving the social skills of deaf students which were divided into three components, namely communication skills, the ability to adapt to the environment, good relationship skills with other people. Keywords: Interpersonal Communication, Deaf Students, Social Skills